Resocjalizacja skazanych z niepełnosprawnością intelektualną w stopniu lekkim z perspektywy dozoru kuratorskiego - Goede, Karolina (Understanding Disability: Issues, Research, Reflections, 2021)
In Poland, the function of social rehabilitation for convicts with intellectual disabilities is implemented by both: the penitentiary and probation system. In prisons there are therapeutic departments adapted to the needs of prisoners’ disabilities. In community supervision, methodology of working with offenders with intellectual disabilities is not regulated by any procedures. This paper presents results of a research focused on the probation service supervision of offenders with mild intellectual disabilities. Difficulties in implementing social rehabilitation tasks, methodology of probation officers’ work, as well as legislative proposals that may improve the probation system in Poland for offenders with mild intellectual disabilities are indicated. The study is based on qualitative methods using the focus panel method. The research group are probation officers for adults from the District Court for Bydgoszcz. The data is analyzed using legal provisions regulating probation service, as well as selected theories and concepts of special education and social rehabilitations of convicts.